2011
DOI: 10.1128/jvi.01412-10
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor-Binding Domain of Influenza Virus Hemagglutinin Produced in Escherichia coli Folds into Its Native, Immunogenic Structure

Abstract: The hemagglutinin (HA) surface glycoprotein promotes influenza virus entry and is the key protective antigen in natural immunity and vaccines. The HA protein is a trimeric envelope glycoprotein consisting of a globular receptor-binding domain (HA-RBD) that is inserted into a membrane fusion-mediating stalk domain. Similar to other class I viral fusion proteins, the fusogenic stalk domain spontaneously refolds into its postfusion conformation when expressed in isolation, consistent with this domain being trappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 42 publications
3
50
0
Order By: Relevance
“…Indeed, H35-C10 is the only HA trimer-dependent MAb we studied that does not detectably bind to HA tops, suggesting that its epitope is dependent on subtle conformational elements that require maintained oligomerization. Intriguingly, DuBois and colleagues (44) demonstrated that the HA Cb antigenic site is subject to considerable conformational flexibility, consistent with the idea that H35-C10 detects a Cb conformation on the HA tops that is unfavorable to association with this MAb. The capacity of HA trimerization-dependent MAbs to bind HA trimer-derived monomers explains our previous observation that these MAbs maintain binding to the HA of acid-triggered virions as measured by hemagglutination inhibition (30).…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, H35-C10 is the only HA trimer-dependent MAb we studied that does not detectably bind to HA tops, suggesting that its epitope is dependent on subtle conformational elements that require maintained oligomerization. Intriguingly, DuBois and colleagues (44) demonstrated that the HA Cb antigenic site is subject to considerable conformational flexibility, consistent with the idea that H35-C10 detects a Cb conformation on the HA tops that is unfavorable to association with this MAb. The capacity of HA trimerization-dependent MAbs to bind HA trimer-derived monomers explains our previous observation that these MAbs maintain binding to the HA of acid-triggered virions as measured by hemagglutination inhibition (30).…”
Section: Discussionmentioning
confidence: 63%
“…3A). The lack of carbohydrates on the bacterially expressed HA1 does not affect the folding and antigenic integrity; almost all of the conventional HA antigenic sites, Sa, Sb, Ca1, Ca2, and Cb, which have been classically characterized using polyclonal mouse antisera (37,38), have good structural integrity and align well with the bacterially expressed and refolded HA1 and full-length HAs from the H1 subtype (4,36) (Fig. 3A).…”
Section: Resultsmentioning
confidence: 98%
“…Eukaryotic expression systems are widely used for the preparation of recombinant HAs, as these proteins have glycans on their N-linked glycosylation sites. However, it has been previously reported that HA1 can be recombinantly produced and refolded from E. coli inclusion bodies with similar biophysical properties to HA produced in insect cells (36). Moreover, E. coli-expressed HA1 has been shown to elicit a protective immune response in ferrets (48), suggesting that a protective antibody response can be generated despite the lack of glycan shielding on the surface of HA, at least in the case of the 2009 H1 pandemic strain.…”
Section: Discussionmentioning
confidence: 99%
“…These diversified Bcell/Ab epitopes include three previously characterized B-cell/Ab epitopes-Sa, Sb, and Ca2-defined by Caton et al by grouping mutants of the influenza virus A/PR/8/34 virus based on their antigenic reactivity to panels of neutralizing monoclonal antibodies (11,12). These epitopes represent distinct neutralizing antigenic regions which have previously been reported to bind to human sera from patients infected with prepandemic H1N1 (24). Thus, this diversifying selection analysis of prepandemic H1N1 HA has identified a subset of experimentally defined H1 HA Bcell/Ab epitopes that appear to be especially important for protective immunity in humans, including the Sa, Sb, and Ca2 Caton epitopes.…”
Section: Resultsmentioning
confidence: 99%